Probabilistic Seismic Hazard Analysis of Pokhara Metropolitan City - Poudel, Sanuta; Chhetri, Pawan; Thapa, Deepak (Journal of Advanced College of Engineering and Management, 2024)
Earthquakes occur randomly in space and time, making accurate predictions challenging. However, estimating earthquake occurrences to a certain extent is possible. This study employs Probabilistic Seismic Hazard Analysis (PSHA) for the Pokhara Metropolitan City. The process involves preparing an earthquake catalog through data collection, homogenization, merging, declustering, and completeness analysis. Subsequently, source characterization identifies seven areal seismic sources: MHT, NG-1, NG-2, NG-3, NE, NW, and South. G-R parameters 'a' and 'b' are then calculated. Finally, ground motion predicting equations are chosen, and site effects in the form of Vs30 values are incorporated. Using R-crisis software, the hazard, expressed as Peak Ground Acceleration (PGA) and spectral acceleration (SA) for 2% and 10% probability of exceedance over 50 years, is computed throughout the Pokhara Metropolitan City.